Navigating conflict of interest in public service: lessons from Kazakhstan - Nauryzbek, Madina; Bokayev, Baurzhan (Frontiers in Political Science, 2025)
The research is aimed at in-depth study of the perception of conflict of interest among public servants of Kazakhstan and finding out how they tend to view this phenomenon as a manifestation of corruption. The objective is to understand how the level of awareness, and education affects the perception of conflicts of interest, and to propose approaches that will help improve regulatory measures. The study employs a mixed methodology, including quantitative, and qualitative data analysis. The research was based on a sociological survey of 10,255 public servants of Kazakhstan, the data of which were analyzed using regression models. According to the study, 82.8% of respondents indicated that difficulties in ensuring compliance with ethical standards contribute to conflicts of interest. At the same time, most respondents associate such conflicts with potential corruption threats. Moreover, regression analysis shows that perceptions of conflict-of-interest policies depend on respondents' understanding and education level. More education leads to critical views on measures, while insufficient understanding impairs perception. The study contributes to the discussion of conflict of interest regulation in the public sector, emphasizing the importance of the educational level and awareness of public servants for effective regulation. The findings are useful for developing more effective anti-corruption and regulatory strategies. Practical implications of the research include updating regulatory policies to address conflict of interest perceptions, enhancing public service ethics through targeted training, and strengthening management and monitoring mechanisms. These measures will improve transparency and thereby increase public trust in government institutions.